Virtual Reality Trends as a New Approach in Architecture Presentation in Indonesia: A Literature Review - Wibowo, Harry; Hutauruk, Denny Meisandy (CV. Publikasi Indonesia, 2024)
Virtual Reality (VR) is now a new trend in architectural presentations in Indonesia, offering an interactive experience that allows for a more detailed visualization of the space before construction. This study aims to explore the trend of VR adoption in Indonesia through a literature review sourced from architectural journals registered in Garba Rujukan Digital (GARUDA). The findings show that VR significantly improves spatial understanding, communication, and collaboration between architects and clients while facilitating faster decision-making. However, factors such as implementation costs and a lack of experts still hinder the widespread use of VR. The study recommends increased investment in VR training and infrastructure and encouraging closer cooperation between academia and the architecture industry to accelerate the adoption of this technology in Indonesia.